2009
DOI: 10.2332/allergolint.08-oa-0034
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Asthma is Associated with Impaired Quality of Life Among Children with Asthma in Japan

Abstract: Existence of EIA among asthmatic children most strongly impairs their QoL. We should be more cautious about the management of EIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 15 publications
0
38
0
Order By: Relevance
“…No difference was found in the total HRQoL sum score between children and adolescents with type I diabetes and healthy peers, whereas QoL scores for school achievement and psychological wellbeing were higher in healthy peers. In another study, Kojima et al, using a Japanese version of KINDL [6], showed that the QoL of children with asthma was significantly impaired.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…No difference was found in the total HRQoL sum score between children and adolescents with type I diabetes and healthy peers, whereas QoL scores for school achievement and psychological wellbeing were higher in healthy peers. In another study, Kojima et al, using a Japanese version of KINDL [6], showed that the QoL of children with asthma was significantly impaired.…”
Section: Discussionmentioning
confidence: 96%
“…We preferred to use the Turkish version of the KINDL questionnaire because there has been no kidney-diseasespecific QoL measurement in Turkish children. Additionally, the questionnaire includes separate generic forms for young children and adolescents, as well as a parent-proxyreport versions [16], and it is also practical and easy to use [3,6,7,13,17,18,22]. In the literature, there many studies in which the KINDL was used as the QoL measure in children with different health problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33][34] In 2003, Hallstrand et al performed a study of high school athletes who were screened by a 7-minute free run for EIB. 31 Of the 256 students who underwent exercise screening, 160 completed the teen version of the pediatric QoL inventory.…”
Section: Burden Of Eibmentioning
confidence: 99%
“…32 Two separate questionnaires were retrieved from 22,645 6-to 7-year-old children and 12,879 13-to 14-year-old children, a response rate of 86 and 64%, respectively. The International Study of Asthma and Allergy on Childhood questionnaire was used to determine the presence of asthma as well as EIB based on questions from the instrument.…”
Section: Burden Of Eibmentioning
confidence: 99%